2009
DOI: 10.1177/0021943608325754
|View full text |Cite
|
Sign up to set email alerts
|

Staging a Team Performance: A Linguistic Ethnographic Analysis of Weekly Meetings at a British Embassy

Abstract: Drawing on insights from Goffman's dramaturgical approach to interaction, this article demonstrates how meetings are team performances routinely concerned with sustaining or challenging interpretations of power relations. The data for this article were collected at a British embassy, relying on participant observation, audio recordings of weekly gatherings of Heads of Section, and interviews with the people that attended the meeting. The analysis focuses on the double role behavior of the Ambassador as the dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…He had to adjust to the goals of the business community, his manager's as well as his own, and thus shift between author, animator, and principal roles (Goffman, 1959) accordingly. The other participants were the audience, occasionally laughing at Tero's humorous acts (Van Praet, 2009). Tero also functioned as an interpersonal and intercultural mediator in the creation of new discourse, because meanings changed in the processes of translation and interpreting.…”
Section: Discussionmentioning
confidence: 99%
“…He had to adjust to the goals of the business community, his manager's as well as his own, and thus shift between author, animator, and principal roles (Goffman, 1959) accordingly. The other participants were the audience, occasionally laughing at Tero's humorous acts (Van Praet, 2009). Tero also functioned as an interpersonal and intercultural mediator in the creation of new discourse, because meanings changed in the processes of translation and interpreting.…”
Section: Discussionmentioning
confidence: 99%
“…The latter are at the core of organizational intentions for holding team meetings in the first place (Cohen, Rogelberg, Allen, & Luong, 2011;Sonnentag, 2001;Van Praet, 2009; see also Reiter-Palmon & Sands, in this volume).…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Beyond the influence on meeting effectiveness, it has been argued that the interaction in team meetings can be seen as a manifestation of team performance. Van Praet (2009) argues that a meeting leader who supervises the meeting process and gives encouragement is important to motivate participants and achieve high team performance. In line with this reasoning, laboratory experiments showed that leadership behavior of facilitating interaction and compromise is related to high perception of group performance (Fox, 1957).…”
Section: Leaders' Position and Success Of Meetingsmentioning
confidence: 99%